Dengue: una causa frecuente de síndrome febril agudo en el Departamento de El Meta, Colombia (2017)
Introduction: Epidemic Dengue fever is an ancient disease, however in the past 17 years, it's activity has a dramatic resurgence of Dengue in the tropics areas worldwide. This increased of epidemic activity, has been associated with the geographical expansion of both, the mosquito vectors and the viruses, the development of hyper-endemicity, and the emergence of Dengue hemorrhagic fever. Objective: The goal of this study was to determine the frequency of Dengue infection in patients with acute febrile syndrome in Meta's Administrative District, Colombia. That ask for a medical advice at the Departmental hospital of Villavicencio. Material and methods: Blood serum were collected from 100 febrile patients in of acute and convalescent stages from the rural and urban zones that arrive for medical advice to the Departmental hospital of Villavicencio during 2013 and 2014. Serologic tests for Dengue (IgM and IgG by ELISA) were performed. Statistical analyses were performed using SPSS 21.0 for Windows (SPSS Inc., USA). The chi-square test was used to make a comparison. Variables that were statistically significant (p<0.05) were kept in the final model. Results: From a total of 100 persons surveyed, (51%) were women, and average age was 23,5 ± 15,6 years, 50% was students and 51 % had some type of Dengue, mainly secondary infections (44 %). Conclusions:Dengue is a frequent infection in Meta Administrative District, Colombia, with a high frequency of exposed population with secondary infection which is a risk factor for severe forms of the disease.